Effect of alternative income assistance schedules on drug use and drug-related harm: a randomised controlled trial - Lindsey Richardson, DPhil; Allison Laing, MA; JinCheol Choi, MSc; Ekaterina Nosova, PhD; M-J Milloy, PhD; Brandon DL Marshall, PhD; Joel Singer, ProfPhD; Evan Wood, ProfMD; Thomas Kerr, ProfPhD (Elsevier, 2021)
Summary: Background: The synchronised monthly disbursement of income assistance, whereby all recipients are paid on the same day, has been associated with increases in illicit drug use and serious associated harms. This phenomenon is often referred to as the cheque effect. Because payment variability can affect consumption patterns, this study aimed to assess whether these harms could be mitigated through a structural intervention that varied income assistance payment timing and frequency. Methods: This randomised, parallel group trial was done in Vancouver, Canada, and enrolled recipients of income assistance whose drug use increased around payment days. The recipients were randomly assigned 1:2:2 to a control group that received monthly synchronised income assistance payments on government payment days, a staggered group in which participants received single desynchronised monthly income assistance payments, or a split and staggered group in which participants received desynchronised income assistance payments split into two instalments per month, 2 weeks apart, for six monthly payment cycles. Desynchronised payments in the intervention groups were made on individual payment days outside the week of the standard government schedules. Randomisation was through a pre-established stratified block procedure. Investigators and statisticians were masked to group allocation, but participants and front-line staff were not. Complete final results are reported after scheduled interim analyses and the resulting early stoppage of recruitment. Under intention-to-treat specifications, generalised linear mixed models were used to analyse the primary outcome, which was escalations in drug use, predefined as a 40% increase in at least one of: use frequency; use quantity; or number of substances used during the 3 days after government payments. Secondary analyses examined analogous drug use outcomes coinciding with individual payments as well as exposure to violence. This trial is registered with ClinicalTrials.gov, NCT02457949. Findings: Between Oct 27, 2015, and Jan 2, 2019, 45 participants were enrolled to the control group, 72 to the staggered group, and 77 to the split and staggered group. Intention-to-treat analyses showed a significantly reduced likelihood of increased drug use coinciding with government payment days, relative to the control group, in the staggered (adjusted odds ratio 0·38, 95% CI 0·20-0·74; p=0·0044) and split and staggered (0·44, 0·23-0·83; p=0·012) groups. Findings were consistent in the secondary analyses of drug use coinciding with individual payment days (staggered group 0·50, 0·27-0·96, p=0·036; split and staggered group 0·49, 0·26-0·94, p=0·030). However, secondary outcome analyses of exposure to violence showed increased harm in the staggered group compared with the control group (2·71, 1·06-6·91, p=0·037). Additionally, 51 individuals had a severe or life-threatening adverse event and there were six deaths, none of which was directly attributed to study participation. Interpretation: Complex results indicate the potential for modified income assistance payment schedules to mitigate escalations in drug use, provided measures to address unintended harms are also undertaken. Additional research is needed to clarify whether desynchronised schedules produce other unanticipated consequences and if additional measures could mitigate these harms. Funding: Canadian Institutes of Health Research, Providence Health Care Research Institute, Peter Wall Institute for Advanced Research, Michael Smith Foundation for Health Research.